CHARACTERISTICS OF SUGGESTIBILITY AND ITS RELATIONSHIP WITH OTHER PSHYCOLOGICAL VARIABLES - González Ordi, Héctor; Miguel-Tobal, Juan José (Anales de Psicología / Annals of Psychology, 1999)
Main results regarding our research line on selfreport assessment of suggestibility are exposed in this paper. First, the most outstanding psychometric data of the Inventory of Suggestibility - I.S. are presented (factor structure, reliability and internal consistency). The I.S. provides a general measure of suggestibility and four subscales: dreaming/ fantasize, absorption, emotional involvement and influencing by others.Secondly, in order to study the divergent validity of the Inventory of Suggestibility, data regarding relationship between suggestibility and other psychological variables are addressed: hypochondriasis, social desirability, Locus of Control and trait anxiety. Results show that there are positive but moderate correlations with hypochondriasis and trait anxiety, and that the I.S. is relatively independent from the psychological variables studied. Third, gender differences related to suggestibility are also remarked because our data suggest that there are significant differences in the sense that females obtained higher mean scores than males in the I.S. This work also explores the relationship between suggestibility and hypnotic susceptibility, remarking that there are weak correlations with motor assessment and moderate correlations with self-report assessment of hypnotic susceptibility.